EFFECTS OF IRON DEFICIENCY ANEMIA AND ITS TREATMENT ON GHRELINS, OBESTATIN AND HEAT SHOCK PROTEIN 70 - Akarsu, S.; Kasar, T.; Akarsu, S.; Aydin, S. (Ferrata Storti Foundation, 2012)
[Abstract Not Available]